Birth weight and maternal energy status during pregnancy as predictors of epigenetic age acceleration in young adults from metropolitan Cebu, Philippines. Issue 11 (2nd November 2022) - Kuzawa, Christopher W.; Ryan, Calen P.; Adair, Linda S.; Lee, Nanette R.; Carba, Delia B.; MacIsaac, Julia L.; Dever, Kristy; Atashzay, Parmida; Kobor, Michael S.; McDade, Thomas W.
ABSTRACT: Epigenetic clocks quantify regular changes in DNA methylation that occur with age, or in relation to biomarkers of ageing, and are strong predictors of morbidity and mortality. Here, we assess whether measures of fetal nutrition and growth that predict adult chronic disease also predict accelerated biological ageing in young adulthood using a suite of commonly used epigenetic clocks. Data come from the Cebu Longitudinal Health and Nutrition Survey (CLHNS), a long-running cohort followed since birth in metropolitan Cebu, Philippines. Past work has shown that birth weight (BW) and the mother's arm fat during pregnancy (a measure of pregnancy energy status) relate inversely to health outcomes in the CLHNS but primarily in males. Genome-wide DNA methylation was assessed in whole blood using the Infinium EPIC array. Participants included males (n=895) and females (n=803) measured in 2005 (20.8–22.5 years). Clocks included the Hannum and Horvath clocks trained on chronological age, the DNAmPhenoAge and DNAmGrimAge clocks trained on clinical biomarkers, the Dunedin pace of ageing (DunedinPACE) clock trained on longitudinal changes in ageing biomarkers, and the DNAmTL clock trained on leukocyte telomere length. In males, lower BW predicted advanced biological ageing using the Hannum, DNAmPhenoAge, DunedinPoAm, and DNAmTL clocks. In contrast, BW did not predict any clock in female participants. Participants' mothers' pregnancy arm fat only predicted DNAmTL in males. These findings suggest that epigenetic clocks are a useful tool for gauging long-term outcomes predicted by fetal growth, and add to existing evidence in the CLHNS for sex differences in these relationships.